Exploring dependence of the patints’ radiation dose on the form of power supply voltage of x-ray tube - Reva, Sergiy; Malakhova, Maryna (Eastern-European Journal of Enterprise Technologies, 2016)
A brief analysis was conducted of organizational and technical methods of reducing the patient’s dose during radiographic examinations that are used in contemporary medicine. The paper considers optimization of the form of power supply voltage of X-ray tube as one of the efficient, but not sufficiently explored, areas of solving this problem. For its analysis, we propose a method of numerical simulation of the process of X-ray screening based on the experimentally obtained data. The results of experimental research are presented. Authors described the methods and results of calculation of influence of the form of power supply voltage of X-ray emitter on the total radiation dose of patients during medical examinations. To model the performance of several types of power units that operate on different physical principles, we created mathematical models that made it possible to calculate the instantaneous and integral values of all electrical parameters of X-ray tube, to find the integral dose of radiation in the plane of patient's location and to simulate a generalized reaction of the X-ray receiver of images on the ray flow that runs through the object of examination. Comparative analysis of the obtained results demonstrated that the total dose of radiation is significantly affected by the design and principle of operation of the power supply unit of X-ray tube, which is a part of the X-ray device. At the equivalent diagnostic quality of images, the difference in the X-ray dose of received by the patient in some modes may exceed 20 %. The assessment we performed indicates the feasibility of modernization of the outdated X-ray equipment with low frequency power units for the purpose of reducing the radiation dose through the improvement in the form of high voltage.